Development Of An Inventory Management Information System Using The Agile Method - Adelia Puspita Sari; Yuntari Purbasari; Andi Chiristian (Jurnal Ilmiah Informatika dan Komputer, 2026)
PT. Saribumi Sriguna Putra still uses manual inventory recording and reporting processes involving ledgers, Microsoft Excel, and direct counts of remaining items in the warehouse. This situation poses risks of recording errors, data duplication, and delays in obtaining inventory information. This study aims to design and develop a web-based inventory management information system to facilitate a more structured process for managing inventory data. The system development method used is Agile Development, which allows the development process to be carried out in stages and adapted to user needs. The development stages include planning, implementation, testing, documentation, deployment, and maintenance. The developed system provides features for inventory data, incoming goods, outgoing goods, as well as reports on inventory, incoming goods, and outgoing goods. The research result is a web-based inventory management information system that can be used to manage inventory data and generate computerized reports. Test results using the Black-Box Testing method indicate that the developed features function in accordance with the system’s intended functions and requirements. This system is expected to assist PT. Saribumi Sriguna Putra in managing inventory data in a more structured manner and supporting the inventory monitoring process.